Processing method affects the nutritional value of low-inhibitor soybeans for nursery pigs - Lewis, A.J.; Jones, D.B.; Giesemann, M.A.; Healy, B.J.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred weanling pigs (16.5 lb avg initial wt) were used in a 35-d growth assay to determine the effects of processing method (roasting in a Roast-A-Tron roaster vs extrusion in an Insta-Pro extruder) on the nutritional value of Williams 82 soybeans with (+K) and without (-K) gene expression for the Kunitz trypsin inhibitor. Treatments were: 1) soybean meal with added soybean oil, 2) + K roasted, 3) + K extruded, 4) -K roasted, and 5) -K extruded. All diets were corn-based and formulated to contain .92% lysine and 3.50 Mcal/kg DE for d 0 to 14 of the experiment and .76% lysine and 3.49 Mcal/kg DE for d 14 to 35 of the experiment. From d 0 to 14, pigs fed extruded soybeans (+K and -K) ate more feed (greater ADFI), grew faster (greater ADG), and were more efficient (better F/G) than pigs fed roasted soybeans. From d 14 to 35 and overall, the same effects were noted, i.e., pigs fed extruded soybeans had greater ADFI and ADG and better F G than pigs fed roasted soybeans. Also, pigs fed -K soybeans were more efficient than pigs fed +K soybeans. The average performance of all pigs fed diets containing the roasted and extruded soybeans was not different from that of pigs fed diets with soybean meal and added soybean oil, although diets with -K extruded soybeans consistently supported numerically greater rates and efficiencies of gain. Extrusion processing yielded soybean products of greater nutritional value than roasting, and -K soybeans were of greater nutritional value than +K soybeans when roasted or extruded.
Keywords: Swine; Soybean; SBM; Processing; Starter; Performance; Trypsin